Association of trait emotional intelligence and individual fMRI‐activation patterns during the perception of social signals from voice and face - Kreifelts, Benjamin (Hum Brain Mapp, 2009)
Multimodal integration of nonverbal social signals is essential for successful social interaction. Previous studies have implicated the posterior superior temporal sulcus (pSTS) in the perception of social signals such as nonverbal emotional signals as well as in social cognitive functions like mentalizing/theory of mind. In the present study, we evaluated the relationships between trait emotional intelligence (EI) and fMRI activation patterns in individual subjects during the multimodal perception of nonverbal emotional signals from voice and face. Trait EI was linked to hemodynamic responses in the right pSTS, an area which also exhibits a distinct sensitivity to human voices and faces. Within all other regions known to subserve the perceptual audiovisual integration of human social signals (i.e., amygdala, fusiform gyrus, thalamus), no such linked responses were observed. This functional difference in the network for the audiovisual perception of human social signals indicates a specific contribution of the pSTS as a possible interface between the perception of social information and social cognition. Hum Brain Mapp, 2010. © 2009 Wiley‐Liss, Inc.